Water management in arid and semi-arid regions interdisciplinary perspectives - Koundouri, Phoebe, 1974-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
The aim of this book is to formulate appropriate strategies and guidelines for water management necessary for the formulation and implementation of integrated sustainable management of water resources. Lessons are learned from various case studies, which examine competing water use patterns, compare governance structures and how these have evolved in response to scarcity, and structural and non-structural instruments to address water deficiency.
pt. 1. Introduction -- pt. 2. A strategy-developing approach for regulating and managing water resources and demand in water-deficient regions : the waterstrategyman project -- pt. 3. A participatory approach to addressing conflicting demands and varying hydrological conditions for the sustainable use of water on Mediterranean islands : the medis project -- pt. 4. An economic approach to integrated and sustainable water resources management in arid and semi-arid regions : a group of environmental economists from the arid cluster -- pt. 5. A co-evolutionary approach to adaptive, integrated water management under changing utilization conditions : the aquadapt project -- pt. 6. Conclusion.
Includes bibliographical references and index.
Keywords: Water-supply -- Management; Arid regions; Electronic books